Effectiveness and user experience of a virtual reality intervention in a cohort of patients with chronic musculoskeletal pain syndromes. - Tiffany Prétat; Pedro Ming Azevedo; Chris Lovejoy; Thomas Hügle (PLOS Digital Health)
Chronic musculoskeletal pain (CMP) syndromes, including fibromyalgia, present diverse physical and psychological symptoms often resistant to pharmacological treatment. To retrospectively evaluate the effectiveness and user experience of Virtual Reality (VR) in reducing pain and anxiety in CMP patients and identify predictors of positive response. Data from 91 CMP patients in a 2-week interdisciplinary pain program were analyzed (78% met fibromyalgia criteria). Pain and anxiety were assessed using Numerical Rating Scales (NRS 0-10) before and after VR. Follow-up interviews were conducted after one month. An unsupervised machine learning model explored response patterns. VR led to a moderate but significant short-term reduction in anxiety and pain (median NRS -1.0, p < 0.001). A reduction of ≥3 NRS points occurred in 25% (anxiety) and 14% (pain). High baseline anxiety (NRS ≥ 7) correlated with greater pain reduction (median -2.0, p = 0.01). After one month, half of the patients reported sustained benefits. Catastrophizing and benzodiazepine use were linked to improved anxiety outcomes. Machine learning identified a most responsive cluster, characterized by patients with nociplastic pain, alexithymia, and anxiety. VR provided moderate short- and mid-term benefits for anxiety and pain in CMP patients, particularly in those with nociplastic pain and high baseline anxiety.